Micropropagation of Lilium candidum L. : a rare and native bulbous flower of Turkey (Bangladesh Journal of Botany, 2013)
Lilium candidum bulb scales were cultured on MS containing different doses and combinations of NAA, BA, Kn and 2iP. Maximum bulblet formation was 88.2% in MS supplemented with 0.1 mg/l NAA + 0.01 mg/l BA and the average number of bulblets per explant was 2.9. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15913 Bangladesh J. Bot. 42(1): 185-187, 2013 (June)